Peak height velocity in young athletes: A longitudinal meta-analysis - Lima, A. B.; Quinaud, R. T.; Gonçalves, C. E.; Carvalho, H. M. (Journal of Sports Sciences, 2023)
The present longitudinal meta-analysis aimed to estimate the growth curves and age at peak height velocity (PHV) in young male athletes, considering anthropometric data from available longitudinal studies. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, studies with repeated measurements in young male athletes were identified from searches across four databases (MEDLINE, SPORTDiscus, Web of Science, and SCOPUS). Estimations were based on multilevel polynomial models using a fully Bayesian framework. After a full-text screening of 317 studies meeting the eligibility criteria, 31 studies were considered. Studies were excluded mainly due to study design, repeated reporting, and incomplete reporting of the outcomes. Of the 31 studies analysed, 26 (84%) focused on young European athletes. The average age at PHV for the total sample of studies with young athletes was 13.1 years (90% credible interval: 12.9; 13.4). When considering data by sport, there was substantial variation in the age at PHV estimates (range: 12.4 to 13.5 years). As most studies in the meta-analysis focused on young European football players (52%), predictions for young athletes from other sports may be limited. The age at PHV in the available data occurred earlier than in general paediatric populations.